Combined effect of esaxerenone and dapagliflozin on aldosterone-mediated sodium reabsorption and potassium excretion - Nakamura, Motonobu; Satoh, Nobuhiko; Mizuno, Tomohito; Takagi, Mayuko; Horita, Shoko; Nangaku, Masaomi (Frontiers in Physiology, 2025)
IntroductionThe efficacy of nonsteroidal mineralocorticoid receptor blockers (MRBs) in inhibiting the progression of diabetic kidney disease (DKD) is well-known. However, MRB therapy often leads to hyperkalemia and remains a major concern. Recent studies suggest that combining potassium-retaining diuretics, renin-angiotensin system inhibitors, and sodium-glucose cotransporter 2 inhibitors (SGLT2i) reduces the incidence of hyperkalemia. However, how SGLT2i, specifically affecting the proximal tubule (PT), suppresses hyperkalemia is unclear. This study aimed to elucidate the interaction between the aldosterone (Ald)/mineralocorticoid receptor (MR) signaling pathway and SGLT2i specifically in the PT, focusing on the synergistic effects on PT sodium (Na+) and potassium (K+) transport activity.MethodsWe investigated the effects of Ald and SGLT2i on PT Na+ and K+ transporters. For PT Na+ transport function analysis, freshly isolated PTs were used to analyze luminal NHE activity and basolateral NBCe1 activity using 2′,7′-bis(carboxyethyl)-5 (6)-carboxyfluorescein acetoxymethyl ester. A DKD model was established using spontaneously diabetic Torii (SDT) fatty rats. The model rats were randomly assigned to the following groups: esaxerenone (Esx) monotherapy and Esx + dapagliflozin (Dapa) therapy. We then evaluated histological parameters, K+ channel expression, and various biological parameters.ResultsAld increased not only the activity of NBCe1 and NHE3 but also the expression of TWIK-1/Kcnk1 and TASK-2/Kcnk5. These stimulatory effects were completely suppressed by ESX. Rats treated with Ald alone exhibited hypertension, hyperinsulinemia, and severe kidney injury, which were ameliorated by ESX; however, these rats also presented with hyperkalemia. The ESX + Dapa therapy reduced the incidence of hyperkalemia and improved kidney injury compared to ESX alone. The expression of TWIK-1 and TASK-2 increased in rats continuously treated with Ald compared with that in control rats, whereas their expression decreased to control levels in rats continuously treated with ESX alone. TWIK-1 expression did not significantly decrease in rats continuously treated with ESX and Dapa compared with that in rats treated with ESX alone.DiscussionThe findings indicate that Ald stimulates Na+ transport via the MR in the PT and regulates the expression of K+ channel genes. The MRB and SGLT2i combination may mitigate MRB-induced hyperkalemia, potentially by regulating TWIK-1 expression and maintaining K+ homeostasis.